Determinants of teenage marital pregnancy among bangladeshi women: An analysis by the cox proportional hazard model - Md Alamgir Sarder; Sharlene Alauddin; Benojir Ahammed (Wolters Kluwer Medknow Publications, 2020)
Introduction: Teenage marital pregnancy is a critical issue responsible for complex and life threatening health problems of both mother and children. This study aimed to determine various demographic, socioeconomic, and spatial factors responsible for teenage pregnancy in Bangladesh. Methods: This study used Bangladesh Demographic and Health Survey 2014 data. A sample of 4,608 teenage (age<20years) married women were included in the analysis. Kaplan Meier Product Limit approach was used to estimate the mean and median teenage pregnancy, and the log-rank test was used to test whether two (or more) groups were equal or not. Finally, Cox proportional hazard model was used to determine the risk factors of teenage pregnancy. Results: Among participants, approximately 90% had experienced teenage pregnancy. The mean (±standard deviation) age of the teenage pregnancy was 17.7 (±2.79) years. Among the demographic and socioeconomic factors, women's and their husband's lower education, lowest wealth index, Islamic faith, unemployment, and no access to mass media were the risk factors associated with the teenage pregnancy. Furthermore, spatial variables, residence in Rangpur division, and rural areas also had higher odds of getting pregnant at teenage. Conclusion: Government should initiate different protective and preventive measures to minimize early marriage and pregnancy, including improvement of female enrolment and completion rate of education, encouragement of female employment opportunities to increase wealth index for women through financial support and technical skill development, and reinforcement family planning utilization using religious texts and knowledge among people at individual and community levels.